Regulatory Gaps and Protection Failures: A Socio-Legal Study of Fraud Cases Involving Indonesian Migrant Workers - Sudarto M. Abukasim; Sutarsa Sutarsa; Dwi Slamet Raharjo; Akbar Nur Salim; Wasino Wasino; Mustafa Mustafa (Journal of Creative Power and Ambition (JCPA), 2026)
International labor migration has become one of the most significant global phenomena in the era of modern globalization. This study aims to analyze the regulatory gap and weak legal protection for Indonesian migrant workers (PMI) in cases of fraud and exploitation of migrant workers. The research uses a socio-legal approach, employing normative analysis of laws and regulations, as well as empirical studies based on court decisions, BP2MI reports, online media, and investigative documents from PMI cases for the 2020–2025 period. Thematic analysis was used to identify patterns of fraud, institutional weaknesses, and socio-legal factors that affect the effectiveness of migrant worker protections. The results of the study show that although Indonesia already has a legal framework through Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, the practice of illegal recruitment and exploitation is still taking place systematically. Forms of fraud include document forgery, use of non-procedural visas, fake employment contracts, wage deductions, passport confiscation, and digital fraud through social media. The study found gaps between formal regulation and implementation, particularly in recruitment supervision, administrative verification, inter-agency coordination, and victim recovery mechanisms. In addition, poverty, low education, lack of legal literacy, and limited employment also increase the vulnerability of migrant workers. Therefore, reform of migrant worker protection is needed by strengthening supervision, institutional reform, digitizing the migration system, and international cooperation.